2020
DOI: 10.1093/pch/pxz169
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for CBME: How often are faculty observing residents?

Abstract: Background The Royal College of Physicians and Surgeons of Canada officially launched ‘Competence by Design’ in July 2017, moving from time-based to outcomes-based training. Transitioning to competency-based medical education (CBME) necessitates change in resident assessment. A greater frequency of resident observation will likely be required to adequately assess whether entrustable professional activities have been achieved. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…One study examining pediatric residents compared the ideal frequency of direct supervision with that of direct supervision. The findings revealed that even senior residents sought more frequent and prolonged direct supervision of core skills crucial to independent practice, such as physical examinations and delivery planning [ 35 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study examining pediatric residents compared the ideal frequency of direct supervision with that of direct supervision. The findings revealed that even senior residents sought more frequent and prolonged direct supervision of core skills crucial to independent practice, such as physical examinations and delivery planning [ 35 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…George et al [35] In the acquisition of fundamental clinical skills, such as history-taking, physical examination, and the delivery of care plans, residents often desired more direct observation than faculty members perceived to be necessary. This preference for direct oversight persisted after they had become senior residents.…”
Section: •Autonomymentioning
confidence: 99%
“…Underpinning efficiency strategies that seek to streamline the CC review process is the assumption that meaningful assessment for learning occurs throughout daily practices of assessment and observation, and thus is not a required aspect of CC work. Although this is certainly the ideal, we know that direct observation of trainees often competes with the demands and structure of clinical service and occurs less frequently than is desired by either faculty members or trainees 41‐43 . Given the many‐faceted challenge of assessment burden, our study advocates for the development of efficiency strategies that leverage data visualisation methods to retain the depth of review when reducing the length of review time.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the CBME model emphasizes more frequent, formative assessment of residents to evaluate their progress towards predefined competencies [ 3 ]. As such, faculty members now have increased responsibility for providing assessments to residents on a more regular basis [ 4 ]. This paradigm shift underscores a growing need for feedback that is specific, constructive, and actionable.…”
Section: Introductionmentioning
confidence: 99%